PAKET MATERI PEMBELAJARAN INKUIRI DALAM PENDIDIKAN LINGKUNGAN HIDUP UNTUK MENINGKATKAN PERILAKU BERWAWASAN LINGKUNGAN SISWA SD DI JAKARTA - Bintang Rumondang Simbolon (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2010)
The objective of the research is to develop an environmental inquiry education material package to increase theenvironmental behavior of the Elementary students. The research was designed by using research anddevelopment (R & D) method. The stages of the research are: (1) to initate the material package, (2) to validatethe materials by using randomized control-group posttest method for every try-out, and (3) to recommend thematerials. In this study, instruments collected important informations such as: (1) need assessment from theteachers, parents and students from Elementary school, (2) environmental behavior possessed by the students.Research findings show that there is a bigger environmental behavior score obtained by inquiry instructionalmaterials treated group compared to conventional method control group. Based on findings, it could beconcluded that the inquiry material package is effective in enhancing the environmental behavior of the students.Therefore, this material package could be recommended for wider application.